Basic Biomechanics with Dynamic Human CD and PowerWeb/OLC Bind-in Passcard - J.Hall Susan (McGrraw-Hill Humanities, 2002)
Basic Biomechanics provides an introduction to biomechanics using the latest findings from the research literature to support and exemplify the concepts presented. Quantitative as well as qualitative examples of problems illustrate biomechanical principles. Quantitative aspects are presented in a manageable, progressive fashion to make biomechanical principles accessible to all students, regardless of their mathematical skills.